Evaluation of efficacy and mechanism of Bacillus velezensis CB13 for controlling peanut stem rot caused by Sclerotium rolfsii - Jia, Shu; Song, Ce; Dong, Hai; Yang, Xujie; Li, Xinghai; Ji, Mingshan; Chu, Jin (Frontiers in Microbiology, 2023)
Peanut stem rot, caused by Sclerotium rolfsii, considerably affects crop productivity. Application of chemical fungicides harms the environment and induces drug resistance. Biological agents are valid and eco-friendly alternatives to chemical fungicides. Bacillus spp. are important biocontrol agents that are now widely used against several plant diseases. This study aimed to evaluate the efficacy and mechanism of a potential biocontrol agent Bacillus sp. for controlling peanut stem rot caused by S. rolfsii. Here, we isolated a strain of Bacillus from pig biogas slurry that considerably inhibits the radial growth of S. rolfsii. The strain CB13 was identified as Bacillus velezensis on the basis of morphological, physiological, biochemical characteristics and phylogenetic trees based on the 16S rDNA and gyrA, gyrB, and rpoB gene sequences. The biocontrol efficacy of CB13 was evaluated on the basis of colonization ability, induction of defense enzyme activity, and soil microbial diversity. The control efficiencies of B. velezensis CB13-impregnated seeds in four pot experiments were 65.44%, 73.33%, 85.13%, and 94.92%. Root colonization was confirmed through green fluorescent protein (GFP)-tagging experiments. The CB13-GFP strain was detected in peanut root and rhizosphere soil, at 104 and 108 CFU/g, respectively, after 50 days. Furthermore, B. velezensis CB13 enhanced the defense response against S. rolfsii infection by inducing defense enzyme activity. MiSeq sequencing revealed a shift in the rhizosphere bacterial and fungal communities in peanuts treated with B. velezensis CB13. Specifically, the treatment enhanced disease resistance by increasing the diversity of soil bacterial communities in peanut roots, increasing the abundance of beneficial communities, and promoting soil fertility. Additionally, real-time quantitative polymerase chain reaction results showed that B. velezensis CB13 stably colonized or increased the content of Bacillus spp. in the soil and effectively inhibited S. rolfsii proliferation in soil. These findings indicate that B. velezensis CB13 is a promising agent for the biocontrol of peanut stem rot.